Impact investment : a practical guide to investment process and social impact analysis + website - Allman, Keith A., 1977-; Escobar de Nogales, Ximena (John Wiley & Sons, Inc., 2015)
Apply a rigorous investment process and integrate social impact analyses to successfully select and invest in social impact investments Impact Investment: A Practical Guide to Investment Process and Social Impact Analysis is a must-read guide for investors and wealth managers entering the social finance investment space known as "impact investing." This book walks readers through the demanding task of properly executing an impact investment strategy, providing solutions to some of the most vexing challenges that arise when investing for both financial return and social impact. Readers will learn how